Response of Liver and Gastric Cancer Cells to Electron and X-ray Radiation (International Journal of Mathematics and Physics, 2025)
Radiotherapy remains a critical pillar of cancer treatment worldwide. This study evaluates the in vitro efficacy of high-energy ionizing radiation, specifically 6 MV electrons and 12 MV X-rays, generated by a Varian Clinac iX linear accelerator (linac), on human HepG2 (liver) and AGS (gastric) cell lines. Cell samples (1 ml) were irradiated with doses ranging from 0.5 Gy to 4 Gy. Cell viability was assessed using the WST assay 4-5 hours post-irradiation. The measured survival rates were critically compared with those predicted using the established linear-quadratic (LQ) model. The results revealed significant and consistent discrepancies between the experimental measurements and the theoretical predictions for both cell lines. For HepG2 cells, the measured survival rate at 4 Gy was higher than the predicted rate. Interestingly, AGS cells irradiated with 12 MV X-rays exhibited minimal cytotoxicity, with a viability rate of 99.0% at 3 Gy versus a predicted rate of 73.6%. These findings suggest a discrepancy between theoretical predictions and the short-term biological responses observed under the shallow in vitro irradiation conditions employed in this study. While the present study was not designed to isolate the underlying mechanisms, the results imply that factors inherent to high-energy beam delivery in thin in vitro geometries, together with the early (four to five hour) post-irradiation assessment window, may have contributed to the limited cytotoxicity observed in both cell lines. Further studies employing extended observation periods or complementary assays would be valuable in clarifying the temporal progression of MV-beam-induced cellular effects.Keywords: Varian Clinac iX, high-energy radiation, HepG2, AGS, cell viability, WST assay, Monitor Unit (MU).